ANALISIS KESESUAIAN PERAIRAN TAMBAK DI KABUPATEN DEMAK DITINJAU DARI NILAI KLOROFIL-A, SUHU PERMUKAAN PERAIRAN, DAN MUATAN PADATAN TERSUSPENSI MENGGUNAKAN DATA CITRA SATELIT LANDSAT ETM 7+ - Muchlisin Arief; Lestari Laksmi W. (Indonesian National Institute of Aeronautics and Space (LAPAN), 2006)
Demak district has 4 sub district that are potentially to develop fishpond such as : Sayung, Karang Tengah, Bonang and Wedung sub district. However, recently the fishpond production is decreasing compared to the production in a few years ago. This decreasing is ceused by water quality degradation and the lage of information on the condition of the fishpond. The aims of the research are : to analyse some parameter for the fishpond suitability such as (cholorophyle-a, water surface temparature and suspended solid load_, 2). to analyse some factors on the fishpond suitability based on water primary productivity such as pH, suspended Oxygen, salinity, Nitrate and phosphate. The result of the research shows that : by using the formulation of klor-a (ug/1)=17.912(b1-b2)/(b1+b2)-0.3343 the range value f chlorophyle-a is 0.368-2,852 ug/1, by using the formulation of Tp(℃)= 0.6674(b6)-75.544 obtained the value of water surface temperature is 25.03-40.00(℃), and by using the formulation MPT(ppm)=-15.8049+0.6674(b1)-1.066(b2)+0.9437(b3)+0.1939(b4), the range value of suspended solid load is 26.07-74.00 ppm. Overlaying the above result (maps of chlorophyll-a, water surface temperature, and MPT) added with the information of water primary productivity obtained that the